ALMA twenty-six arcmin2 survey of GOODS-S at one millimeter (ASAGAO): Millimeter properties of stellar mass selected galaxies. (30th June 2020) - Yamaguchi, Yuki; Kohno, Kotaro; Hatsukade, Bunyo; Wang, Tao; Yoshimura, Yuki; Ao, Yiping; Dunlop, James S; Egami, Eiichi; Espada, Daniel; Fujimoto, Seiji; Hayatsu, Natsuki H; Ivison, Rob J; et al.
Abstract: We make use of the ALMA twenty-Six Arcmin 2 survey of GOODS-S At One-millimeter (ASAGAO), deep 1.2 mm continuum observations of a 26-arcmin 2 region in the Great Observatories Origins Deep Survey-South (GOODS-S) obtained with Atacama Large Millimeter/sub-millimeter Array (ALMA), to probe dust-enshrouded star formation in K -band selected (i.e., stellar mass selected) galaxies, which are drawn from the FourStar Galaxy Evolution Survey (ZFOURGE) catalog. Based on the ASAGAO combined map, which was created by combining ASAGAO and ALMA archival data in the GOODS-South field, we find that 24 ZFOURGE sources have 1.2 mm counterparts with a signal-to-noise ratio >4.5 (1σ ≃ 30–70 μJy beam −1 at 1.2 mm). Their median redshift is estimated to be z median = 2.38 ± 0.14. They generally follow the tight relationship of the stellar mass versus star formation rate (i.e., the main sequence of star-forming galaxies). ALMA-detected ZFOURGE sources exhibit systematically larger infrared (IR) excess (IRX ≡ L IR / L UV ) compared to ZFOURGE galaxies without ALMA detections even though they have similar redshifts, stellar masses, and star formation rates. This implies the consensus stellar-mass versus IRX relation, which is known to be tight among rest-frame-ultraviolet-selected galaxies, cannot fully predict the ALMA detectability of stellar-mass-selected galaxies. We find that ALMA-detected ZFOURGE sources are the main contributors to the cosmic IR star formation rate density at z = 2–3.